Investigating Social Media Strategies by Brands on Facebook and Instagram - Dunn, Katharine (The IIE, 2016)
Widespread internet connection and easy access has led to a generation of individuals who spend a considerable amount of their time online making use of various social networking sites such as Facebook, Twitter and Instagram. This has created a new opportunity for brands to connect with their consumers and has essentially changed the way we market products and services. This research report has taken this into account and has looked at the various marketing strategies employed by brands on networks such as Facebook and Instagram. A strong textual analysis of pre-existing literature, combined with qualitative research in the form of online surveys with consumers has shown that there are several aims and motivations of owning and running a branded social media page for a business. In order for brands to hold a strong presence online and in the minds of their online customers, posts either need to serve functional, social, psychological, hedonic or monetary needs for the consumer. Fundamentally, brands need to ensure that their pages serve their target audience whilst creating brand awareness and maintaining a positive area for engagement as this ultimately builds trust in a brand and leads to brand loyalty. In a day and age where technology is ever changing and social networking sites are in today and out tomorrow, it is important for brands to find which platforms gives them the best reach as well as to know what strategies solicit the responses they are looking for.
Keywords: Social media; Social networking